NOTE - Prediction of genotypic values of maize for the agricultural frontier region in northeastern Maranhão, Brazil - Emmanuel Arnhold; Freddy Mora; Cleso Antônio Patto Pacheco; Hélio Wilson Lemos de Carvalho (Crop Breeding and Applied Biotechnology, 2012)
Agricultural research, mainly focused on the evaluation of maize cultivars along agricultural frontiers, are scarce. This study assessed 128 maize genotypes in the agricultural frontier region of the State of Maranhão, between 2008 and 2009. The experiment was arranged in a lattice design with two replications. The genotypes were evaluated for grain yield in a mixed model, with fixed intercept and experimental effects. The random effects were genotype, genetic class (single-, double or triple-cross hybrid and variety), and incomplete block/replication/ environment. The genotype effect was significant by the likelihood ratio test in all models, highlighting the genotypic values of the single-cross hybrids DKB177, AG8088 and DKB390, the triple-cross PL6882, the double-cross BM502 and of the open-pollinated variety SHS3031.